The Turtle House : a novel - Churchill, Amanda (Harper, an imprint of HarperCollinsPublishers, 2024)
In 1999 Texas, Lia Cope, when her grandmother Mineko moves in, connects with her over stories of the Turtle House in Japan and the secrets they both carry, and when Mineko is forced to live in an assisted living community, she and Lia devise a plan to bring a beloved lost place to life.